Investigating the usefulness of chitosan based proton exchange membranes tailored with exfoliated molybdenum disulfide nanosheets for clean energy applications. (15th March 2019) - Divya, Kumar; Rana, Dipak; Alwarappan, Subbiah; Abirami Saraswathi, Meenakshi Sundaram Sri; Nagendran, Alagumalai
Graphical abstract: Highlights: Chitosan/Exfoliated molybdenum disulfide composite membranes were fabricated for use in direct methanol fuel cells. Chitosan-0.75% membrane showed higher proton conductivity (2.92 × 10 −3  Scm −1 ) and membrane selectivity (8.9 × 10 4  Scm −3  s). Chitosan-0.75% membrane exhibited lower methanol permeability of 3.28 × 10 −8  cm 2  s −1 . Tailored chitosan nanocomposite membranes found to be a proficient alternative to costly Nafion. Abstract: Chitosan based proton exchange membranes (PEMs) has been synthesized by a facile solution casting strategy using two-dimensional exfoliated molybdenum disulfide (E-MoS2 ) nanosheets. The prepared PEMs are characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Field-emission scanning electron microscopy (FESEM) with Energy dispersive X-ray spectroscopy (EDX), water uptake, Thermogravimetric analysis (TGA), AC impedance spectroscopy and cyclic voltammetry. In comparison with pure chitosan membrane, E-MoS2 nanosheets incorporated membranes exhibit excellent water absorbing capacity, ion-exchange capacity and proton conductivity. Moreover, the changes in roughness of nanocomposite membranes is investigated by atomic force microscopy (AFM) and the results confirm that the E-MoS2 nanosheets content enhances the surface roughness as well as provide good mechanical and thermal resistivity to the chitosan/E-MoS2 membranes. Chitosan membranes with 0.75% E-MoS2 nanosheets demonstrated higher proton conductivity of 2.92 × 10 −3  Scm −1 and membrane selectivity of 8.9 × 10 4  Scm −3  s with reduced methanol permeability of 3.28 × 10 −8  cm 2  s −1 . Overall, results evidenced that the chitosan/E-MoS2 nanocomposite membranes will be an alternate to Nafion in direct methanol fuel cells (DMFCs).